A política de municipalização do ensino fundamental no estado do Pará a partir da ótica dos gestores estaduais da educação - ALVES, Charles Alberto de Souza (Universidade Federal do Pará, 2012)
This study presents from the point of view of managers of state education, as the policy of decentralization of primary education (re) configured in Para during the period 1996 to 2010. Aims to analyze how governments occurred throughout the state, the process of (re) formulation, identifying the speeches which were used in guiding decision making of this policy and presents the most significant impact of the policy of decentralization to improve the quality of education The key in Pará study used document analysis and semi-structured interviews with managers of state governments who worked at the State Secretariat of Education of Para The study concluded that the policy of decentralization is configured in various ways over the Governments the PSDB and the PT. In this policy the Government of the PSDB is configured as an indispensable condition for the management of public education to reach the desired quality. In the PT government there have been several attempts to reformulate the policy, through seminars and forums, but the lack of clarity about the state government that wanted to change this policy and the five Secretaries of Education led to the emergence of several different discourses about this policy and the discontinuity of referrals that were presented by their respective Secretaries.